Astronomy for Amateurs - Flammarion, Camille; Al Arabi, Hassan; Al Sawee, Akmal (Monufia, Egypt Hawadeet, 2024)
Amateur astronomy, also called backyard astronomy and stargazing, is a hobby whose participants enjoy watching the night sky (for sunspots, eclipses, etc.), mainly with portable telescopes. Even though scientific research is not their main goal, many amateur astronomers make a contribution to astronomy by monitoring variable stars, tracking asteroids and discovering transient objects, such as comets. This book is a perfect introduction to Astronomy for amateurs
Keywords: Astronomy